Selecting Manufacturing Sampling Plans for New and Existing Processes. - Taylor, Wayne A.; Ingram, David J. (Journal of Validation Technology (JVT))
This article is intended for process validation practitioners and pertains to selecting acceptance sampling plans, including rejection quality level (RQL), in a product manufacturing setting. The authors assume readers have a basic understanding of acceptance sampling including single and double attribute sampling and variables sampling plans. The reader should be familiar with the terms acceptance quality level (AQL) and RQL, also known as lot tolerance percent defective (LTPD). Two excellent book references are provided at the end of this article for those wanting more information.